Analysis of Factors Associated with the Incidence of Hypertension in Pregnancy: Study at RSUD dr. H. Andi Abdurrahman Noor, Tanah Bumbu Regency - Kasmasari, Kasmasari; Bakhriansyah, Bakhriansyah; Al Audhah, Nelly; Suhartono, Eko; Syahadatina, Meitria (Journal La Medihealtico, 2024)
Hypertension is one of the diseases that often threatens pregnancy that occurs after 20 weeks of gestation. Tanah Bumbu is one of the regencies in South Kalimantan Province with 75 cases of maternal mortality rate (MMR) in 2022. To asses the relationship between maternal age, parity, body mass index (BMI), history of hypertension, and stress with the incidence of hypertension in pregnancy (HiP) in RSUD dr. H. Andi Abdurrahman Noor Tanah Bumbu Regency. This is an analytic observational study using a cross sectional approach with 85 samples using the purposive sampling technique. The research instruments were questionnaires. The dependent variable was: the incidence of HiP, while independent variables were: maternal age, parity, BMI, history of hypertension, and stress. Prevalence Odds Ratios (PORs) and 95% Confidence Intervals (95% CIs) were determined by using bivariate and multivariate analysis using binomial logistic regression tes. The results showed that there was an association between age (p=0.000), BMI (p=0.030), history of hypertension (p=0.000), and stress (p=0.000) and HiP, but not for parity (p=0.087). The stress was mostly associated with the incidence of HiP (Adj. OR= 1.964; 95% CI 2.816-79.516, p value=0.001). There was a relationship between maternal age, BMI, history of hypertension, and stress, but there was no relationship between parity and the incidence of HDK. The variable most associated with the incidence of HiP is stress.